2002
DOI: 10.1046/j.1532-5415.2002.50251.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on Complications from Cardiac Surgery in the Oldest Old

Abstract: In the geriatric population, subjects with lower BMI have a higher risk of complications and death from cardiovascular surgery than subjects with higher BMI. An increased BMI does not increase the risk of complications from cardiovascular surgery, with the exception of wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…A high risk of surgery-related perioperative complications in obese patients has been reported in studies performed for several surgical subspecialties [4][5][6]. But in patients undergoing coronary artery bypass surgery, a low body mass index (BMI) is associated with an increased risk of perioperative complications and the only increased risk in old patients with a high BMI was sternal wound infection [7][8][9]. Blee et al [10] also reported that obesity was not associated with postoperative mortality or morbidity in patients undergoing colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A high risk of surgery-related perioperative complications in obese patients has been reported in studies performed for several surgical subspecialties [4][5][6]. But in patients undergoing coronary artery bypass surgery, a low body mass index (BMI) is associated with an increased risk of perioperative complications and the only increased risk in old patients with a high BMI was sternal wound infection [7][8][9]. Blee et al [10] also reported that obesity was not associated with postoperative mortality or morbidity in patients undergoing colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between BMI and its effect on postoperative CABG is controversial: some studies found no significance between high BMI and mortality [13][14][15][16]; others have shown a positive correlation between obesity and postoperative complications [17][18][19]. Gurm et al [20] found a short-term protective effect of obesity in patients who had undergone CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is thought to be a risk factor for perioperative morbidity in patients undergoing cardiac surgery, however, data from cohort of subjects with an average age of 62 years has shown that, with the exception of sternal wound infection, obesity does not predispose to postoperative complications after CABG 23 .…”
Section: Discussionmentioning
confidence: 96%